PEMAAFAN DITINJAU DARI PENILAIAN TERHADAP PERISTIWA MENYAKITKAN DALAM HUBUNGAN INTERPERSONAL ERAT (Studi Pada Mahasiswa Psikologi Islam Fakultas Ushuluddin dan Pemikiran Islam Tahun Pertama) - Budiman Budiman (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2015)
Man is social creature who needs others in order to preserve his life and interaction. Sometimes man has some mistake and get the disappoint situation and hard treatment. But not all peoples want to forgive other’s mistake and to let it go. The process of forgiveness needs hardworking, self-determination and mental practice because human has very fluctuant and dynamic soul which is reactive against outside stimulant.